Pengaruh Pembiayaan Mudharabah, Musyarakah Dan Murabahah Terhadap Profitabilitas (Roa) Pt. Bank Syariah Mandiri, Tbk Periode 2009-2016 - Ariyani, Lucy; , Ir. Maulidiyah Indira Hasmarini,MS (2017)
This study aims to analyze the effect of financing Mudharabah, Musyarakah and Murabahah the level of PT. Bank Syariah Mandiri, Tbk. The period 2009 through 2016 using the ratio of return on assets simultaneously profitablility and partially. Data are obtained from the quarterly financial statements 1 to 4 for 6-year period. Methods of data analysis used in this study is the regression of time series data Eviews program. The results of this study indicate that the financing is partially positive and significant impact on the level of ROA, in contrast with the partial musyarakah significant negative effect on the level of ROA, murabahah financing does not affect significantly the level of ROA. Keywords : Mudharabah financing, musyarakah, murabahah and profitability (ROA).